2022
DOI: 10.1214/20-ba1254
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Quickest Detection of Credit Card Fraud

Abstract: This paper addresses the risk of fraud in credit card transactions by developing a probabilistic model for the quickest detection of illegitimate purchases. Using optimal stopping theory, the goal is to determine the moment, known as disorder or fraud time, at which the continuously monitored process of a consumer's transactions exhibits a disorder due to fraud, in order to return the best trade-off between two sources of cost: on the one hand, the disorder time should be detected as soon as possible to counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
2
1
Order By: Relevance
“…In what seems to be at variance with the cybercrime trends, where card fraud has been regarded as the major cyber threat to the retail business by previous studies (Mugari and Olutola, 2021; Buonaguidi, 2019; SABRIC, 2018; KPMG, 2015), findings from this study reveal that card fraud is not as prevalent as threats such as virus dissemination and hacking. This may possibly be explained by the fact that payment cards are widely used in the developed countries than in the developing countries.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In what seems to be at variance with the cybercrime trends, where card fraud has been regarded as the major cyber threat to the retail business by previous studies (Mugari and Olutola, 2021; Buonaguidi, 2019; SABRIC, 2018; KPMG, 2015), findings from this study reveal that card fraud is not as prevalent as threats such as virus dissemination and hacking. This may possibly be explained by the fact that payment cards are widely used in the developed countries than in the developing countries.…”
Section: Discussioncontrasting
confidence: 55%
“…Longstanding research has identified card fraud as one of the dominant forms of cybercrime affecting the retail sector and this is largely due to the adoption of payment cards as the major electronic payment system (Mugari and Olutola, 2021; Buonaguidi, 2019; SABRIC, 2018; KPMG, 2015). According to Mugari and Olutola (2021), card fraud comes in four types, namely, card not present fraud, counterfeit card fraud, lost or stolen card fraud and application fraud.…”
Section: Introductionmentioning
confidence: 99%
“…In the finance industry the prediction of credit card fraud (cf. Buonaguidi et al 2022), stock market anomalies and insurance claim fraud (cf. Gomes et al 2021) are the most common examples of anomaly detection (see Phua et al 2010 for a survey of fraud detection).…”
Section: Introductionmentioning
confidence: 99%